Proposed algorithm for return to sports in competitive athletes who have suffered COVID-19 - Oikonomou, E.; Papanikolaou, A.; Anastasakis, A.; Bournousouzis, E.; Georgakopoulos, C.; Goudevenos, J.; Ioakeimidis, N.; Kanakakis, J.; Lazaris, G.; Papatheodorou, S.; Tsatsopoulou, A.; Tsonou, P.; et al. (Hellenic Journal of Cardiology, 2020)
Coronavirus disease 2019 (COVID-19) is an acute respiratory disease of various severity caused by the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). The cardiovascular system is the second most significant target of COVID-19 and involvement includes acute myocardial injury, myocarditis, arrhythmias, and venous thromboembolism. Reports document that in patients with COVID-19, the incidence of myocardial injury is estimated at 28% and is associated with fatal outcome.4 In the acute phase of myocarditis, exercise may exacerbate viral replication, inflammation, myocardial cell death, arrhythmias, and may adversely affect the outcome leading to morbid complications.